High flow cytometric scores identify adverse prognostic subgroups within the revised international prognostic scoring system for myelodysplastic syndromes. (30th June 2014) - Alhan, Canan; Westers, Theresia M.; Cremers, Eline M. P.; Cali, Claudia; Witte, Birgit I.; Ossenkoppele, Gert J.; van de Loosdrecht, Arjan A.
Summary The estimation of survival of myelodysplastic syndromes (MDS) and risk of progression into acute myeloid leukaemia is challenging due to the heterogeneous clinical course. The most widely used prognostic scoring system (International Prognostic Scoring System [IPSS]) was recently revised (IPSS‐R). The aim of this study was to investigate the prognostic relevance of flow cytometry (FC) in the context of the IPSS‐R. Bone marrow aspirates were analysed by FC in 159 patients with MDS. A flow score was calculated by applying the flow cytometric scoring system (FCSS). Patients were assigned to IPSS and IPSS‐R risk groups. The FCSS correlated with the World Health Organization classification, IPSS and IPSS‐R risk groups. Mild flow cytometric abnormalities were associated with significantly better overall survival (OS) and lower risk of disease evolution. The presence of aberrant myeloid progenitors was associated with transfusion dependency and disease progression. Most importantly, the FCSS identified prognostic subgroups within the IPSS‐R cytogenetic good risk and low risk group. Flow cytometric analysis in patients with MDS provides additional prognostic information and is complementary to the IPSS‐R. The addition of a flow cytometric score next to the clinical parameters within the IPSS‐R is a further refinement of prognostication of patients with MDS.